Early Versus Delayed Antiretroviral Therapy and Cerebrospinal Fluid Fungal Clearance in Adults With HIV and Cryptococcal Meningitis - Bisson, Gregory P.; Molefi, Mooketsi; Bellamy, Scarlett; Thakur, Rameshwari; Steenhoff, Andrew; Tamuhla, Neo; Rantleru, Tumelo; Tsimako, Irene; Gluckman, Stephen; Ravimohan, Shruthi; Weissman, Drew; Tebas, Pablo (Clinical infectious diseases, 2013)
Background. The burden of Cryptococcus neoformans in cerebrospinal fluid (CSF) predicts clinical outcomes in human immunodeficiency virus (HIV)—associated cryptococcal meningitis (CM) and is lower in patients on antiretroviral therapy (ART). This study tested the hypothesis that initiation of ART during initial treatment of HIV/CM would improve CSF clearance of C. neoformans. Methods. A randomized treatment-strategy trial was conducted in Botswana. HIV-infected, ART-naive adults aged ≥21 years initiating amphotericin B treatment for CM were randomized to ART initiation within 7 (intervention) vs after 28 days (control) of randomization, and the primary outcome of the rate of CSF clearance of C. neoformans over the subsequent 4 weeks was compared. Adverse events, including CM immune reconstitution inflammatory syndrome (CM-IRIS), and immunologic and virologic responses were compared over 24 weeks. Results. Among 27 subjects enrolled (14 control and 13 intervention), the median times to ART initiation were 7 (interquartile range [IQR], 5–10) and 32 days (IQR, 28–36), respectively. The estimated rate of CSF clearance did not differ significantly by treatment strategy (−0.32 log 10 colony-forming units [CFU]/mL/day ± 0.20 intervention and −0.52 log 10 CFUs/mL/day (± 0.48) control, P = .4). Two of 13 (15%) and 5 of 14 (36%) subjects died in the intervention and control arms, respectively (P = 0.39). Seven of 13 subjects (54%) in the intervention arm vs 0 of 14 in the control arm experienced CM-IRIS (P = .002). Conclusions. Early ART was not associated with improved CSF fungal clearance, but resulted in a high risk of CM-IRIS. Further research on optimal incorporation of ART into CM care is needed. Clinical Trials Registration. NCT00976040.